Experimental study on resistance stability and durability of road active deicing conductive Ethylene Propylene Diene Monomer rubber composites. Issue 2 (March 2020) - Wei, Haibin; Ma, Zipeng; Han, Shuanye
Abstract: Active deicing is the main way to deal with snow and ice disaster now. In order to realize the purpose of active heating deicing, a kind of Ethylene Propylene Diene Monomer (EPDM) multilayer composite with conductivity is proposed in this paper. The resistance stability of conductive EPDM rubber composite is measured after pressure sensitivity, freezing-thawing cycle and high-temperature tests. The results show that the conductive EPDM rubber composite developed in this paper has good compression stability and good resistance durability after low temperature freezing-thawing cycle and high-temperature test.